Use of Meloxicam or Ketoprofen for Piglet Pain Control Following Surgical Castration - Viscardi, Abbie V.; Turner, Patricia V. (Frontiers in Veterinary Science, 2018)
Surgical castration of piglets is performed routinely on commercial pig farms, to prevent boar taint and minimize aggression. While this procedure is known to be painful, piglets are generally not provided any analgesic for pain relief, leading to welfare concerns. The objectives of this study were to assess the efficacy of two nonsteroidal anti-inflammatory drugs (NSAIDs), meloxicam (MEL) (0.4 mg/kg or 1.0 mg/kg) and ketoprofen (KET) (6.0 mg/kg) in reducing behavioral indicators of pain in castrated piglets. This study also examined the utility of the Piglet Grimace Scale (PGS) as a pain assessment tool. Nineteen litters of 5-day-old male piglets (n = 120) were used and piglets within a litter were randomly assigned to one of eight possible treatments: 0.4 mg/kg MEL-castrated or uncastrated, 1.0 mg/kg MEL-castrated or uncastrated, 6.0 mg/kg KET-castrated or uncastrated, saline (castrated control) or sham (uncastrated control). Treatments were administered intramuscularly 20 min prior to surgical castration. Piglets were video recorded for 1 h pre-procedure, for 8 h immediately post-castration and for another hour, 24 h post-procedure. Twenty-one behaviors and postures were scored continuously for the first 15 min of each hour and 1156 still images of piglet faces were collected and scored using the PGS. Within each treatment group post-castration, castrated piglets displayed significantly more pain-related behaviors than uncastrated piglets (0.4 mg/kg MEL: p = 0.0339, 1.0 mg/kg MEL: p = 0.0079, 6.0 mg/kg KET: p = 0.0034, Controls: p < 0.0001). Castrated piglets also grimaced significantly more post-procedure than uncastrated piglets (p = 0.0061). Compared to the castrated control, none of the NSAID treatments significantly reduced piglet pain behaviors (0.4 mg/kg MEL: p = 1.0000, 1.0 mg/kg MEL: p = 0.9995, 6.0 mg/kg KET: p = 0.4163) or facial grimacing. Piglets demonstrated significantly more pain behaviors 24 h post-castration than at all other time points (p < 0.0001). The PGS was a less effective measure to detect acute pain; however, our findings suggest it does have utility as a pain assessment tool in neonatal pigs. Our findings also indicate that the use of these NSAIDs were ineffective at alleviating castration-associated pain in piglets.